SEJARAH BERDIRINYA PARTAI POLITIK TAREKAT ISLAM DI BUKITTINGGI 1945-1975 - Muhammad, Fandy; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Absrak: Political Parties Islamic Tarekat is one of the political parties that was established in 1945 after Indonesia's independence. Political Parties The Islamic Tarekat stands in accordance with the appeal of the vice president Moh. Hatta, which was stated in the Government Declaration No. X November 3, 1945. During the physical revolution, the Political Parties of the Islamic Tarekat participated in the formation of the Barata Tentara Allah (BATA) which was directly commanded by party supporters, Sheikh H Jalaluddin. Political Parties This Islamic Tarekat is quite clever to play its role as a political party by trying to approach the government to establish relations with non-party organizations to get votes in the elections. During the course of the Political Party the Islamic Tarekat was not free from conflicts from either the external party or internal party. To find out the history of the establishment of the Political Party of the Islamic Tarekat, the method used is qualitative which is a research method whose findings and sources are not obtained from statistical procedures or other counts. The respondents from this study were figures from the PPTI, members of the PERTI organization, and relatives related to the founder. Data collection techniques used are interviews, documentation and books related to PPTI.Keywords: Political Party of Islam (PPTI), Sheikh H Jalaluddin, PERTI, Indonesia 1945-1975